Productive housing for self-sufficient communities - Paolo Cascone; Maddalena Laddaga; Filippo Orsini (Techne, 2025)
Due to the consequences of climate change and the Ukrainian conflict, nearly 42 million people across Europe could not afford to heat their homes properly in 2022. Beyond the political debate on the energy price cap, as recently suggested in the European Green Deal project, refurbished and new sustainable buildings in the EU will need to pave the way for a clean and affordable energy system. The paper will focus on a scientific design methodology based on a comparative analysis of case studies in the field of self-sufficiency, energy and food production in collective housing. The theoretical frame is based on a diachronic vision of relations between energy, food, architecture, and its production chains as drivers for innovative and integrated design processes. This also aims to develop alternative economic models where communities could become more accountable, share resources, and self-produce their energy and food, shifting their role from consumers to producers.